2022
DOI: 10.1016/j.heliyon.2022.e08852
|View full text |Cite
|
Sign up to set email alerts
|

Immediate enteral nutrition can accelerate recovery and be safe in mild acute pancreatitis: A meta-analysis of randomized controlled trials

Abstract: Han, W. Wang, Immediate enteral nutrition can accelerate recovery and be safe in mild acute pancreatitis: a meta-analysis of randomized controlled trials, HELIYON, https://doi.org/10.1016/j.heliyon.2022.e08852. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Finally, both studies do not mention the actual caloric intake per day, which is a better reflection of the nutritional status. Two recent meta-analyses confirmed that early diet resumption is associated with short hospital stay [14,15].…”
Section: Nutritionmentioning
confidence: 96%
“…Finally, both studies do not mention the actual caloric intake per day, which is a better reflection of the nutritional status. Two recent meta-analyses confirmed that early diet resumption is associated with short hospital stay [14,15].…”
Section: Nutritionmentioning
confidence: 96%
“…enteral nutrition (various definitions) [mean difference (95% confidence interval, 95% CI): 2.57 (0.4-4.72); P ¼ 0.02] [13].…”
Section: Key Pointsmentioning
confidence: 99%
“…Finally, a recent meta-analysis of five RCTs ( n = 372) showed that immediate enteral nutrition defined as feeding initiated just after admission was associated with a statistically significant decrease in the length of hospitalization compared with early enteral nutrition (various definitions) [mean difference (95% confidence interval, 95% CI): 2.57 (0.4–4.72); P = 0.02] [13].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Additionally, some authors recently reported that immediate oral feeding is feasible, safe and may accelerate recovery. [5,7–9]…”
Section: Introductionmentioning
confidence: 99%
“…[1] Additionally, some authors recently reported that immediate oral feeding is feasible, safe and may accelerate recovery. [5,[7][8][9] Accordingly, we designed the present clinical trial to assess whether home monitoring is effective, safe and non-inferior to hospitalization for managing mild AP.…”
Section: Introductionmentioning
confidence: 99%